Current and potential geographical distribution of white balsum Heliocarpus americanus L. in the department of Nariño - Lagos B., Tulio César; Ordoñez J., Héctor; Castillo M., Alvaro; Navia E., Jorge Fernando; Lagos S., Liz Katherine; Benavides C., Carlos; Andrade D., Danita; Duarte A., David Esteban; López G., Dalia Julieth (Revista de Ciencias Agrícolas, 2014)
This investigation was designed to establish the geographical distribution of H.americanus in the department of Nariño, from georeferencing information analysis and identification of possible bioclimate zones where the species is found. Nineteen climate parameters and the known distribution of the species were evaluated, obtained by georeferencing174 sites in 15 municipalities of the department of Nariño. The most likely distribution of the species is found at altitudes between 1350 and 2550 meters. There are three climate distribution groups: group one with 148 points, group two with 21 points, and group three with five points. The three groups are similar in terms ofhumidity. We obtained a 90% chance of having suitable environmentsfor this species along the Andes mountain range, which shows suitable climate zones for the species’ development. In addition, there are small areas where its distribution has lost continuity, creating isolated populations.